1990
DOI: 10.1002/ajp.1350210403
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the diet of lowland gorillas at Lopé in Gabon

Abstract: This report describes the composition of the diet of lowland gorillas, Gorilla gorilla gorilla, at Lope in central Gabon. This population inhabits mature evergreen tropical forest and is not habituated to human observers. Data were collected during 6 years of an ongoing long-term study, from feeding-trails and by direct observation, but mostly by fecal analysis. Gorillas ate 182 plant foods from 134 species and 36 families. The fruit diet was diverse: 95 species were consumed, most with succulent pulp, and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(107 citation statements)
references
References 32 publications
5
102
0
Order By: Relevance
“…It has been suggested that primary lowland forests, because they largely lack terrestrial herbaceous vegetation (THV) are poor gorilla habitat resulting in low gorilla population densities in these forests [Schaller, 1963;Groves, 19711. More recent studies have shown that in the west African lowland forests gorillas attain high densities [Tutin & Fernandez, 1985;Carroll, 1988;Fay, 1989;Fay et al, 19901 and that THV is often abundant in primary forest [Rogers and Williamson, 1987;Rogers et al, 1990;Fay et al, 19901 [Fay, unpublished data]. This study supports the notion that gorilla densities are geographically correlated with the abundance of THV.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It has been suggested that primary lowland forests, because they largely lack terrestrial herbaceous vegetation (THV) are poor gorilla habitat resulting in low gorilla population densities in these forests [Schaller, 1963;Groves, 19711. More recent studies have shown that in the west African lowland forests gorillas attain high densities [Tutin & Fernandez, 1985;Carroll, 1988;Fay, 1989;Fay et al, 19901 and that THV is often abundant in primary forest [Rogers and Williamson, 1987;Rogers et al, 1990;Fay et al, 19901 [Fay, unpublished data]. This study supports the notion that gorilla densities are geographically correlated with the abundance of THV.…”
Section: Discussionsupporting
confidence: 76%
“…While the western lowland gorilla (G. g. gorilla) is more frugivorous than other subspecies of gorilla, the majority of its diet is derived from the stems and leaves of a limited number of species of monocotyledonous herbs [Sabater Pi, 1977;Tutin & Fernandez, 1985;Calvert, 1985;Rogers & Williamson, 1987;Rogers et al, 1988Rogers et al, , 1990Carroll, 1988;Fay, 1989;Fay et al, 1990;Williamson et al, 19901. It has been suggested that primary lowland forests, because they largely lack terrestrial herbaceous vegetation (THV) are poor gorilla habitat resulting in low gorilla population densities in these forests [Schaller, 1963;Groves, 19711.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed folivory/frugivory Williamson et al, 1990;Tutin and Fernandez, 1993;Nishihara, 1995;Remis, 1997 …”
Section: Gorilla Gorilla Gorillamentioning
confidence: 99%
“…W estern lowland gorillas (Gorilla gorilla gorilla Savage et Wyman, 1847) occur in the tropical rain forest of west central Africa and Gabon shelters a significant population (Tutin & Fernandez, 1984 bach, 1779) began in the Lopé Reserve, in central Gabon, in 1983 and is on-going (e. g. Tutin et al, 1991;Williamson et al, 1990). The study area of 50 km 2 is isolated and researchers are the only humans present.…”
Section: Introductionmentioning
confidence: 99%